2011
DOI: 10.1021/jp207291k
|View full text |Cite
|
Sign up to set email alerts
|

Glass Transition Dynamics of Room-Temperature Ionic Liquid 1-Methyl-3-trimethylsilylmethylimidazolium Tetrafluoroborate

Abstract: The conductivity relaxation dynamics of the room-temperature ionic liquid 1-methyl-3-trimethylsilylmethylimidazolium tetrafluoroborate ([Si-MIm][BF(4)]) have been studied by broadband conductivity relaxation measurements at ambient pressure and elevated pressures up to 600 MPa. For the first time, several novel features of the dynamics have been found in a room-temperature ionic liquid. In the electric loss modulus M″(f) spectra, a resolved secondary β-conductivity relaxation appears, and its relaxation time τ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 62 publications
2
92
0
Order By: Relevance
“…Recently in a study of the conductivity relaxation dynamics of the roomtemperature ionic liquid, 1-methyl-3-trimethylsilylmethylimidazolium tetrafluoroborate ([Si-MIm][BF4]), a prominent and well resolved conductivity β-relaxation was observed [19]. The broadband conductivity (σ) relaxation measurements at ambient pressure and elevated pressures up to 600 MPa found an approximate co-invariance of τ σβ , τ σα , and (1 − n) in this neat ionic liquid glass-former.…”
Section: Johari-goldstein Relaxation Of Rigid Polar Probes In Apolar mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently in a study of the conductivity relaxation dynamics of the roomtemperature ionic liquid, 1-methyl-3-trimethylsilylmethylimidazolium tetrafluoroborate ([Si-MIm][BF4]), a prominent and well resolved conductivity β-relaxation was observed [19]. The broadband conductivity (σ) relaxation measurements at ambient pressure and elevated pressures up to 600 MPa found an approximate co-invariance of τ σβ , τ σα , and (1 − n) in this neat ionic liquid glass-former.…”
Section: Johari-goldstein Relaxation Of Rigid Polar Probes In Apolar mentioning
confidence: 99%
“…Here τ σα and τ σβ stand for the conductivity α-and β-relaxation times. The CM is applicable to ion conductivity relaxation, and successful in accounting for experimental data in many ionically conducting materials [4,18,19,[47][48][49] with the same Eq. (3) and relation (4), but with τ σ0 , τ σβ , and τ σα replace the corresponding quantities in there.…”
Section: Johari-goldstein Relaxation Of Rigid Polar Probes In Apolar mentioning
confidence: 99%
“…6, we verify the approximate agreement between s s0 (T g ) and s sb (T g ), and thus conrm that the conductivity b-relaxation present is in accord with the CM prediction as found before in other ionic conductors. 15,25,26,36,46 From the good agreement of the secondary conductivity relaxation and the secondary dipolar relaxation times shown in Fig. 6, we have concluded that there is translation-rotation coupling.…”
Section: 2628-38mentioning
confidence: 54%
“…To resolve the issue and conrm the presence of the secondary conductivity relaxation, we used the Coupling Model (CM). 15,25,26,36,46 Originally, the CM was applied to secondary relaxations having properties strongly connected to the structural a-relaxation. The existence and universal presence of this kind of secondary relaxation, called the Johari-Goldstein (JG) b-relaxation, was suggested by its analogy to the primitive relaxation of the CM, which started in a paper 47 in 1998, and has since been extensively developed.…”
Section: 2628-38mentioning
confidence: 99%
See 1 more Smart Citation